Kunstens betydning? Utvidede perspektiver på kunst og barn & unge - Skregelid, Lisbet; Nødtvedt Knudsen, Kristian (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Why do children and young people need art? How do we rationalize the significance of art in society? This anthology is based on research carried out by members of the multidisciplinary research group Art and Young People at the Faculty of Fine Arts of the University of Agder in Kristiansand. The contributing authors argue in favor of research into children's and young people's actual experience of art and artistic practices as well as issues within the arts that affect them indirectly. The book's subtitle indicates a desire to employ a wider understanding of the notions of art and childhood and youth, which is also evident in the themes, content and research approaches it includes. The chapters span both children's and young people's interaction with visual art, music, theater within and outside the context of preschool, school and extracurricular programs, and projects that are more on the periphery of these areas. The authors are thus not just interested in the importance of art to children and young people, but to society in general as well. This anthology is aimed at readers across a broad spectrum of academic disciplines, but will also be of interest to all those concerned with art's place and meaning in schools, in society, and in research itself.